1986
DOI: 10.1530/jrf.0.0770655
|View full text |Cite
|
Sign up to set email alerts
|

Acetate and plasma cholesterol as progesterone precursors in the intact ovary of the Day-16 pregnant rat

Abstract: Rats at Day 16 of pregnancy were infused, via the parametrial artery, with radioactively labelled acetate or cholesterol. All of the venous effluent was collected and examined for radioactive progesterone and related compounds. Labelled progesterone was found in the venous effluent within 15 and 30 min of the start of cholesterol and acetate infusions, respectively, which shows that the ovary can extract both precursors from blood and convert them to progesterone in the intact animal. However, the proportion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…Blood-borne cholesterol appears to be physiologically important for luteal func¬ tion in the cow, because elevated serum cholesterol values result in increased progesterone concen¬ trations during the luteal phase (Talavera et ai, 1985). Circulating cholesterol is probably the preferred substrate, as opposed to de-novo synthesis of cholesterol, in many species (see review by Gwynne & Strauss, 1982;Swann & Bruce, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Blood-borne cholesterol appears to be physiologically important for luteal func¬ tion in the cow, because elevated serum cholesterol values result in increased progesterone concen¬ trations during the luteal phase (Talavera et ai, 1985). Circulating cholesterol is probably the preferred substrate, as opposed to de-novo synthesis of cholesterol, in many species (see review by Gwynne & Strauss, 1982;Swann & Bruce, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…A second explanation may relate to a change in the supply of cholesterol for steroidogenesis, since the de novo synthesis of cholesterol via the 3-hydroxy-3-methylgutaryl coenzyme A reductase enzyme also occurs on the SER (Azhar et al, 1985). Although studies in vivo have shown that this route of cholesterol supply for luteal steroidogenesis is quantitatively insignificant at day 16 of rat pregnancy (Swann and Bruce, 1986), it is not clear how much cholesterol is derived via this conversion on day 22. If the amount of de novo cholesterol synthesis does change with advancing pregnancy, it could mask any relationship that might exist between luteal ultrastructure and the amount of steroid secreted.…”
Section: Discussionmentioning
confidence: 99%
“…Samples for steroid assay were stored at -10°C until assayed. At the end of the experiments both ovaries were removed and the corpora lutea of pregnancy were separated from those of the previous cycles as previously described (Swann & Bruce, 1986) and analysed for progestagen and total cholesterol content.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis. Progesterone and 20a-dihydroprogesterone determinations were carried out by RIA as previously described (Swann & Bruce, 1986). Intra-and inter-assay coefficients of variation were 61% and 100% respectively for progesterone and 4-5% and 11 4% respectively for 20a-dihydroprogesterone.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation